Cover crops effect at three drying moments on consumptive wateruse, nitrogen dynamics, and late corn crop yield (Semiárida, 2022)
In order to evaluate the effect of when we kill the cover crop on the yield of a late corn, under the hypothesis that as the desiccate date is delayed, it will increase the carbon sequestration the amount of nitrogen (N) immobilized in the biomass (lower C/N ratio) and weed suppression and it will reduce the water soil storage for the next crop. Trials established in completely randomized blocks with four repetitions of the following treatments: 1st drying date (july), 2nd drying date (august) and 3rd drying date (september), in turn, each plot was divided in half to establish treatments with and without nitrogen fertilization in the corn crop. Total water (AT), aerial production and carbon and nitrogen; root biomass production, consumptive use (UC), water use efficiency (WUE) and nitrogen availability and yield were determined. The results obtained in the treatment of the 1st drying date were: production of air biomass of the CC of 3015 Kg MS.ha-1, production of root biomass of the CC of 1765 Kg.ha-1, UC of 237 mm, USA of 12.2 Kg.ha-1.mm-1 and corn yield of 6566 Kg.ha-1. For the treatment 2 nd drying date were: production of aerial biomass of the CC of 5060 Kg MS.ha-1, production of root biomass of the CC of 6352 Kg.ha-1, UC of 260 mm, USA of 20 Kg.ha-1 mm-1 and corn yield of 6450 Kg.ha-1. Finally, for the treatment of the 3rd date of drying were: production of aerial biomass of the CC of 8252 Kg MS.ha-1, production of root biomass of the CC of 4000 Kg.ha-1, UC of 347 mm, USA of 24.2 Kg.ha-1 mm-1 and corn yield of 5931 Kg.ha-1. The drying time of the CC have an influence on the yield in the Pampean Semi-Arid Region, given a moisture regime of the Utic type, typical of that region.
Keywords: entisol; semi-arid region; water use efficiency